All Children Reading (USAID, World Vision and the Australian Governmen t) eKitabu-Case-Study 2021 (eKitabu, 2021)
A case study detailing eKitabu's participation in the All Children Rea ding (ACR) Grand Challenge, focusing on its development of accessible digital content and sign language materials for children with disabili ties in Africa, along with key learnings and sustainability prospects.
Keywords: Org:eKitabu